Effect of Flow Disruptors on the Performances of a Cantilever Piezoelectric Energy Harvester - Rubino, Edoardo; Meciej, Jordan (Journal of Vibration Testing and System Dynamics, 2026)
This study aims to determine the effect of a flow disruptor on the performances of a cantilever piezoelectric energy harvester invested by an airflow. The purpose of the flow disruptor is to increase the turbulence intensity of the incoming flow and therefore the momentum transferred to the piezoelectric beam. The height of the flow disruptor and the distance between the flow disruptor and the energy harvester were investigated to determine the optimal configuration. Results indicate that for an energy harvester with a frontal area of $\mathrm{\sim}$18 cm${}^{2}$ (7 cm by 2.54 cm), the flow disruptor should have a height of 4 cm and should be placed 13 cm away from the harvester. Also, a shift in the frequency of vibration occurs when the flow disruptor is placed in front of the harvester.